Dynamic Personality Science. Integrating Between-Person Stability and Within-Person Change - Nadin Beckmann (Frontiers Research Topics, 2017)
Personality can be understood from at least two perspectives. One focuses on stable, between-person differences, or traits. The other perspective focuses on within-person differences and dynamics, i.e., fluctuations in personality in response to situations and across time. This Research Topic reflects recent developments in personality research to integrate both trait and dynamic perspectives. An integrated view on personality recognizes both stability in between-person differences and within-person change. Contributors are drawn from research teams across Europe, North America and Australasia, and from basic and applied fields, including organizational, educational, and clinical. The studies reported provide new evidence in support of an integrative approach, highlight currently active areas of research and propose new directions of research. Current streams of research include the study of contingent units of personality and within-person processes underlying traits, the comparisons of findings based on within- vs. between-person data, the conceptualisation and operationalization of perceived and objective change in situation variables, the malleability of personality and the potential for personality interventions. Integrative approaches using within-person designs provide new, bottom-up insights into general principles of personality that explain differences between people while reflecting the complexities of within-person personality dynamics at the level of the individual.